(untitled) (Academicia Globe: Inderscience Research, 2023)
This article discusses modern game technologies of teaching, in particular foreign language vocabulary. Difficulties of using games in foreign language lessons are highlighted and methodological recommendations for teachers on the effective organization of game activities are offered.